Analisis Kebijakan Perbedaan Lama Waktu Mendapatkan Pekerjaan Antara Masyarakat Terdaftar Dan Tidak Terdaftar Kartu Prakerja Dalam Penurunan Pengangguran di Kota Batam - Salvia, Eka; Ulpa, Maria; Halid, Risca Marsanti (Gorontalo State University, 2026)
This study aims to analyze the difference in the length of time to get a job between people registered and not registered with pre-employment cards in reducing unemployment in Batam City with 50 respondents. Unemployment is a problem that often occurs and needs serious attention. So it is hoped that the pre-employment card program can reduce poverty. This study uses a descriptive approach with primary data obtained through interviews with people registered and not registered with the Pre-Employment Card Program. The research results show that the Pre-Employment Card Program does not have a significant influence on the length of time looking for work in Batam City. With the result that the average time to look for work for people who register for a pre-employment card is 6.75 with a variance of 12.64. Meanwhile, people who are not registered have an average time of 6.93 with a variance of 12.51. The statistical test results show that the t-count value -0.25 is smaller than the t-table of 1.66 and 1.98, so H0 is accepted.